2018
DOI: 10.1002/slct.201800015
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Theory and In Vitro Photodynamic Activities of New Copper(II)‐Histidinito Complexes

Abstract: The photo‐dynamic effect of four new copper(II)‐histidinito complexes with phenanthroline‐based ligands were studied in details. All the complexes were tested against HeLa (Human Cervical Carcinoma) and 3T3 (normal fibroblast) cells both in dark and in visible light. Although the complexes were toxic to HeLa cells (IC50 ∼ 10 μM), visible light (400‐700 nm) remarkably enhanced the cytotoxicity of the complexes to the extent of sub‐micromolar level. Several photo‐physical measurements along with the Time‐depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The activity of the ligands decreased in the following order: A ≈ B ≫ C. While A and B showed similar cytotoxicity in the low-micromolar concentration range, ligand C was noncytotoxic, possibly due to its poor solubility in DMSO (≤0.2 mM). It should be noted that it was previously reported that dppz and its analogues were devoid of any anticancer activity against different cancer cell lines, 25,39,40 with the exception of ligand A, which was moderately cytotoxic against the HeLa cell line (IC 50(24 h) ≈ 60 μM). 39 The majority of the tested Ru complexes exhibited improved aqueous solubility but modest anticancer activity, similar to previously published Ru-dppz complexes.…”
Section: Synthesis Of [(ηmentioning
confidence: 94%
See 1 more Smart Citation
“…The activity of the ligands decreased in the following order: A ≈ B ≫ C. While A and B showed similar cytotoxicity in the low-micromolar concentration range, ligand C was noncytotoxic, possibly due to its poor solubility in DMSO (≤0.2 mM). It should be noted that it was previously reported that dppz and its analogues were devoid of any anticancer activity against different cancer cell lines, 25,39,40 with the exception of ligand A, which was moderately cytotoxic against the HeLa cell line (IC 50(24 h) ≈ 60 μM). 39 The majority of the tested Ru complexes exhibited improved aqueous solubility but modest anticancer activity, similar to previously published Ru-dppz complexes.…”
Section: Synthesis Of [(ηmentioning
confidence: 94%
“…It should be noted that it was previously reported that dppz and its analogues were devoid of any anticancer activity against different cancer cell lines, 25,39,40 with the exception of ligand A, which was moderately cytotoxic against the HeLa cell line (IC 50(24 h) ≈ 60 μM). 39 The majority of the tested Ru complexes exhibited improved aqueous solubility but modest anticancer activity, similar to previously published Ru-dppz complexes. 17,19,21,25,26,41,42 Only 3A and 3C were cytotoxic in the low micromolar range in MDA-MB-231 and HCT116 cell lines in agreement with their higher aqueous stability.…”
Section: Inorganicmentioning
confidence: 94%
“…21,22 The poor aqueous solubility and stability, bioavailability and rapid metabolism, absorption, degradation in biological medium and bad pharmacokinetic/ pharmacodynamic (PK/PD) properties in vivo in addition to the low thermal and photo-stability of curcumin, however, limit its clinical efficacy. [23][24][25] Complexation of curcumin with the transition metal ions coordinated through a β-diketo group not only enhances the aqueous stability of the curcumin, but has also shown remarkable photochemotherapeutic activities by generating cytotoxic ROS. [26][27][28][29][30] Over the last two decades, the coordination compounds of heavy metals (Ru, Pt, Ir, Rh, Os) in lieu of first-row transition metals have been given significant importance because of their kinetic inertness in biological media, ligand-tunable redox properties and luminescence properties in biological matrix, for their potential application in photochemotherapy, cellular imaging and theranostics.…”
Section: Introductionmentioning
confidence: 99%
“…The strategic use of red light for generating singlet oxygen ( 1 O 2 ) from molecular oxygen ( 3 O 2 ) in the presence of a photosensitizer for tumor ablation had emerged as a noninvasive and target-specific treatment modality for cancer in the early 1980s, and the treatment was popularly known as photodynamic therapy (PDT). Photofrin is a first-generation photosensitizer or a PDT drug, approved by the FDA, and is clinically used primarily against esophageal cancer. Hepatotoxicity, skin-photosensitivity of the PDT agents, and the unavailability of an effective photosensitizer are the major concerns for effective photochemotherapeutic applications. Transition-metal complexes and nanoconjugates, generating reactive oxygen species (ROS) on photoexcitation with higher-wavelength light, have emerged as viable and alternative solutions for photochemotherapeutic applications. Iron­(III) generally forms less-labile and thermodynamically stable complexes with the π-donor ligands, e.g., carboxylate-O or phenolate-O. The complexation of iron­(III) with the π-donor ligands in an octahedral geometry typically results in a reduced energy gap between t 2g and e g * molecular orbitals that lead to low-energy metal-centered or ligand-to-metal charge-transfer (LMCT) transition with the typical wavelength of absorption in the range of 450–600 nm. When such complexes are activated with light at the LMCT band, there is typical homolytic fission of the metal–ligand bond, which consequently leads to the oxidation of the ligand (carboxylate-O or phenolate-O) and reduction of the iron­(III) center to iron­(II). Such a light-induced intramolecular redox reaction is typically responsible for the generation of extremely cytotoxic ROS, such as superoxide anions (O 2 •– ) and hydroxyl radicals. Therefore, the ability of the phenolate or carboxylate-based complexes of iron­(III) to yield ROS with low-energy or longer-wavelength light activation has shown potential as a promising strategic tool for photochemotherapeutic utility.…”
Section: Introductionmentioning
confidence: 99%